Antibacterial studies and phytochemical constituent of long beans coats vigna unguiculata / Sharifah Nurulain Syed Jamalludin - Syed Jamalludin, Sharifah Nurulain (Faculty of Applied Sciences, 2016)
The used of Vigna unguiculata or long beans has been used as an ulam in Malaysia. It can be easily obtain from the local market in Asia and also Malaysia. This study was aimed to evaluate the antibacterial properties and phytochemical constituent of the of Vigna unguiculata coats. The antibacterial activity of the methanol extract of Vigna unguiculata coats was tested against gram-positive and gram-negative bacteria by using the disc diffusion method. In addition, the phytochemical constituent of the Vigna unguiculata coats which were phlobatannins, terpenoid and flavonoids were also tested. In this study, the methanol coats extract of Vigna unguiculata showed no inhibition zone towards all tested bacteria. The result indicated that the coats extract of Vigna unguiculata all the tested bacteria showed no inhibition zone. This study suggested that the coats extract of Vigna unguiculata may have no or very little antibacterial properties. On the other hand, phytochemical constituent of the Vigna unguiculata showed the present of flavonoids and terpenoid and absent of phlobatannins.